(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper presents an innovative five-layered architecture for finding equitable representation across the various fragmented sections of large datasets. The architecture employs a set of customizable criteria to group together similar datasets into well-balanced unbiased sample sets; while retaining complete and accurate metadata for all file boundary elements. Important features of this architecture include: a multi-level criteria engine which is capable of processing accepted and rejected streams from a variety of sources; a stratified sampling process which effectively eliminates the presence of partition skew; and a quality assurance mechanism that provides an efficient means to capture and report performance-related metrics. Benchmark partitioning results indicate a significant shift toward overall balance ratio improvements; with improvements of approximately 1.75 to 1.12 ratio, as well as an overall reduction in volume anomaly of 87% (from ±25% down to ±3.2%), and total absence of schema drift occurred at a cost of less than 5% of the overall dataset processing costs to the author(s). By implementing this method, the processing of large datasets has been made much more reliable than previously possible, while simultaneously minimising bias and maximising the ability to provide efficient audit trial capabilities. Future enhancements to the architecture will focus on providing distributed execution capabilities in conjunction with streaming integration into enterprise data systems.